Selling Transracial Adoption Families, Markets, and the Color Line - Raleigh, Elizabeth (Temple University Press, 2018)
"Chosen Children" examines the role of the adoption marketplace in shaping how transracial adoptive families are sorted and matched, and analyzes what these practices suggest about race in the United States. In contrast to previous work on race and adoption markets that focus on the experiences of adoptive parents, Raleigh's project focuses on adoption workers--social workers, attorneys, and counselors. Taking a market approach that treats adoptive parents as consumers and children as commodities, Raleigh brings together interviews with adoption practitioners, participant observation at adoption information sessions, and adoption statistics in order to demonstrate how the downturn in supply of "adoptable honorary white children" (which she defines as Asian and hispanic children) led to the increased popularity of the transracial adoption of foreign-born and biracial black children.